Understanding Social Support Throughout the Injury Process Among Interuniversity Swimmers - Alisa Abgarov; Sarah Jeffery-Tosoni; Joseph Baker; Jessica Fraser-Thomas (University of Kansas Libraries, 2012)
The purpose of this study was to gain comprehensive understanding of athletes' social support experiences during the injury process, with a focus on social support networks, exchanges, and appraisals (Bianco & Eklund, 2001). Twelve university swimmers who recently experienced swimming-related injuries engaged in a semistructured interview. Findings indicate athletes had mixed experiences with their networks of social support (i.e., coaches, medical practitioners, parents, and teammates), with themes regarding exchanges and appraisals emerging in three categories: (a) Don't bring your negative energy to practice, (b) Show me you care, and (c) Provide me with some clear and appropriate direction! Participants reported coaches and teammates being in denial of their injuries, shunning them from the team, or pushing them to train through their injuries, resulting in athletes feeling uncared for, unsupported, and lacking direction. Athletes' sense of support stemmed from feeling cared for. Findings underscore the importance of comprehensively examining the multiple constructs of social support, while serving as a springboard for further investigations and important practical implications.